Behavior Intention towards the Adoption of Innovative Household Sanitary Ware: A Case Study of Jakarta, Indonesia - Adhiutama, Akbar (The Asian Journal of Technology Management (AJTM), 2011)
This study tried to describe the behavior intention factors related to adopt the innovative bidet toilet seats in the households. The increase of the middle class population in Indonesia creates a new demand for adopting innovative products to enhance lifestyles. There were many electronic home appliance products have been easily adopted in Jakarta households, however there has been low adoption for electronic bidet toilet seats in household bathrooms. This study aims to identify and analyse the critical factors involved in adopting these seats in households and to explore the relative significance of each of these factors. It reports the results of empirical tests conducted regarding the non users’ adoption of these seats, based on the extended Theory of Planned Behavior. This study was administrated to 115 participants in Jakarta. Descriptive statistic, correlation analysis and multiple regressions were performed to determine the important factors. The results indicate that intention, voluntariness, observability, water usage and age are positively influence the adoption of the seats in urban households in Jakarta. Keywords: behavior adoption, electronic bidet toilet seats, urban households, jakarta